Responsiveness to reduced dosage of rituximab in Chinese patients with neuromyelitis optica - Yang, Chun-Sheng (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To determine the effect of a lower dose of rituximab in depleting B lymphocytes, maintaining low B-cell counts, and relapse in patients with neuromyelitis optica (NMO) and NMO spectrum disorders. METHODS: We treated 5 Chinese patients with deteriorating NMO and NMO spectrum disorders with a 100-mg IV infusion of rituximab once a week for 3 consecutive weeks, followed by additional infusion of the same dosage depending on circulating B-cell repopulation. RESULTS: This reduced dosage of rituximab was sufficient to deplete B cells and maintain low B-cell counts. None of the treated patients experienced relapse, and all patients exhibited stabilized or improved neurologic function during the 1-year follow-up period. MRI revealed the absence of new lesions, no enhancement in spinal cord and brain, a significant shrinkage of spinal cord segments, and a reduction/disappearance of previous brain lesions. CONCLUSION: A lower dosage of rituximab may be sufficient in depleting B cells, maintaining low B-cell counts, and preventing disease progression in Chinese patients with NMO.